PENGARUH KUALITAS PELAYANAN KARYAWAN FRONT OFFICE TERHADAP KEPUASAN TAMU MENGINAP DI HOTEL THE AXANA PADANG - Mefri, Happy; Yuliana, Yuliana; Abrian, Youmil (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aims to determine the effect of service quality to the Front Office employee satisfaction Hotel guests staying at Axana Padang . This type of research is associative causal . The population in this study is the average number of guests staying ie 1,711 people per month . The number of samples in this study are numbered 95 people were taken using the formula Riduwan . The sampling technique is non-probability sampling , ( incidental sampling ) . Collecting data using a questionnaire based on Likert Scale which has proven its validity and reliability . Results of linear regression analysis sedarhana obtained F count with sig . 0.005 < 0.05 , then the variable can explain the variable service quality customer satisfaction significantly , with R Square of 0.083 . This means that service quality affects customer satisfaction by 8.3 % and 91.7 % influenced by other factorsKeyword: Quality, Service , Employee , Satisfaction , and Guests.